An Efficient Synthesis of Functionalized 2H-1,3,5-Oxadiazines via Metal-Carbenoid-Induced 1,2,4-Oxadiazole Ring Cleavage - Strelnikova, Julia O.; Rostovskii, Nikolai V.; Khoroshilova, Olesya V.; Khlebnikov, Alexander F.; Novikov, Mikhail S. (Synthesis, 2020)
A high-yielding method for the synthesis of 2H-1,3,5-oxadiazines by rhodium(II)- or copper(II)-catalyzed reaction of 1,2,4-oxadiazoles with α-diazo esters has been developed. The reaction proceeds via attack of the metallocarbenoid on the oxadiazole N2 atom followed by ring opening/1,6-electrocyclization and enables the introduction of alkyl, aryl, oxy, and amino substituents into the 6-position and electron-withdrawing groups into the 2-position of 1,3,5-oxadiazine. The N2-attack and the N4-attack of the carbenoid cause different oxadiazole ring openings, which are controlled by the substitution at C5. The presence of a substituent at this position is a prerequisite for the N2-attack to occur, leading to the formation of 1,3,5-oxadiazines.
Keywords: diazo compounds; oxadiazoles; oxadiazines; rhodium; catalysis; carbenoids